At home in Mitford (Mitford, ,, 2008)
Father Tim, a bachelor rector in the small hill town of Mitford, North Carolina, gets more than he bargained for when he yearns for more excitement in his life and suddenly finds himself dealing with a large dog, a very attractive new neighbor, a jewel thief, and an unloved boy.

A light in the window (Mitford, ,, 1996)
Father Tim, a bachelor rector living in a small town, gets more than he bargained for when he finds himself dealing with a very attractive neighbor, a wealthy widow, and his uninvited cousin.

These high, green hills (Mitford, ,, 1997)
Father Timothy Kavanagh, married for the first time at the age of sixtysomething, struggles to deal with the upheaval and delight of having a wife, while also presiding over the triumphs and troubles of the people of the small town of Mitford, North Carolina.

Out to Canaan (Mitford, ,, 1998)
It looks like change is coming to the little town of Mitford with Father Tim and his wife contemplating retirement, a pushy candidate challenging the long-time mayor, the Sweet Stuff Bakery on the verge of closing, and a real estate agent trying to open a spa.

A common life: the wedding story (Mitford years, ,, 2001)
The inhabitants of Mitford gather together for the long awaited wedding of Father Tim Kavanagh and Cynthia Coppersmith.

In this mountain (Mitford, ,, 2002)
Father Tim Kavanagh, retired and living back in Mitford, finds himself becoming depressed and discontent with his idle life, especially as his wife Cynthia's career as a children's book author is taking off, and when a health crisis strikes, he finds himself depending on others for a change.

Light from heaven (Mitford, ,, 2005)
Father Timothy Kavanagh has been commissioned to resurrect a long-empty mountain church and has been given an angel to help in the process.